College Students’ Opinions About Coping Strategies for Mental Health Problems, Suicide Ideation, and Self-Harm During COVID-19 - Klonoff-Cohen, Hillary (Frontiers in Psychology, 2022)
Background Mental health problems have emerged as a significant health complication in US colleges during COVID-19, and have been extensively investigated globally. In contrast, research on coping among the college population during the pandemic is scant. Objectives The purpose of this preliminary study was to obtain undergraduate college students’ feedback/opinions about coping strategies for mental health problems, suicide ideation, and self-harm during COVID-19 attending a Midwestern university. Methods In December 2021, 104 undergraduate students completed an online survey on coping strategies using Qualtrics. Results The most beneficial coping strategies for mental health ranked by college students were: 1) a skills training development program (30%), 2) meditation (19%), and 3) mindfulness exercises (15%). Best coping strategies for preventing self-harm and suicide ideation/behaviors during COVID-19 were ranked as: 1) improving friends’ support, (32%), 2) building self-esteem (29%), and 3) addressing anger, depression, stress, and loneliness (25%). Finally, one-half of participants felt parents should be involved in interventions. The most important types of support from parents were: 1) emotional support (31%), 2) direction/assistance with solutions (27%), and problem-solving (16%). Conclusion Potential avenues which could be implemented into future interventions include: i) training undergraduate students to employ more effective skills training, mindfulness or meditation strategies; ii) integrating mental health, suicide, and self-harm prevention into the curriculum; iii) offering more in-person campus services targeted toward the psychological and emotional effects of a pandemic, and iv) involving support persons (e.g., parents, friends) in students’ lives which could enhance their well-being during and after COVID 19.